The formation of new compounds - A. Gasparoli (Grasas y Aceites)
The formation of new compounds The study of model systems allows us to reconstruct the complex mosaic of reactions which make up the frying process. In particular such systems, if made up of single oils or their components, verify the transformation of the triglyceride matrix by thermo-oxidizing treatment. Should this then have added specific substrates (protein, starch) they reconstruct the oil-substrate interaction and the influence of the same substrate in the transformation. The contribution of the information is equally distributed between the volatile products and the complex products; in fact both contribute to indicate the reactions in play, supporting the previous considerations for investigation at an analytical level. The present work discusses the newly formed products (volatile or nonvolatile), verifying in particular the formation of reaction products with the substrates.